Analisis Ekonomi Politik Korupsi di Perusahaan Listrik Negara (Sebuah Tinjauan dari Perspektif Teori Kleptokratik terhadap Kasus Listrik Swasta PLTU Paiton I) - Ulul Albab (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
In Indonesia, corruption has been so endemic inside the country that it affects everyone from the village level to the center of power in Jakarta. Massive corruption has been blamed as one of the causes of Indonesia's economic stagnation that occurred after the Asian Economic Crisis. Why corruption is so prevalent and what factors make corruption so prevalent in Indonesia?. This letter try to explain the causes of endemic corruption in Indonesia with three theories: mainstream economic theory, patrimonialism, and kleptocratic state theory. This tulisan also try to discussion about the distinguish between